Cognitive model of numerology - Досымбекова, Р.Ө.; Кенжебаева, А.А. (Journal of Oriental Studies, 2022)
This article is devoted to numerology, one of the most ancient sciences, which studies the symbolic value and meaning of numbers. The article narrates, that numerology is closely interrelated with such sciences as philosophy and astrology, that ancient people resorted to numerology for understanding the concept of mysterious natural phenomena and their inner world, as well as for solving other environmental problems. The magical aspects of numerology, numerological classifications and various numerical codes are described. The ethnolinguistic side of numerology is analyzed on the basis of researches and opinions of scientists-numerologists. Key words: numerology, astrology, cosmos, symbol, culture.